Comparative analysis of gut microbiota in metabolic syndrome and obese children from Southeastern China - Wang, Jingjing; Zhuang, Peifeng; Lin, Bin; Zheng, Jinlu; Li, Haiqing; Tang, Wenlin; Ye, Wenbin; Chen, Xiangjian; Zheng, Mingping (Frontiers in Microbiology, 2024)
The prevalence of childhood obesity is rising globally, with some obese children progressing to develop metabolic syndrome (MS). However, the specific differences between these groups remain unclear. To investigate the differences in gut microbiota, we conducted physiological and biochemical assessments, alongside 16S rRNA sequencing, in a cohort of 32 children from Southeastern China, which included 4 normal-weight children, 5 with mild obesity, 9 with moderate obesity, 9 with severe obesity, and 5 with metabolic syndrome. Our results indicated that waist circumference, serum triglycerides, total cholesterol, non-HDL levels, and the prevalence of fatty liver were significantly elevated in both obese and MS children compared to their normal-weight peers, with the MS group exhibiting more pronounced abnormalities. Conversely, HDL levels showed a contrasting trend. Additionally, alpha diversity of gut microbiota increased with weight, while beta diversity analysis revealed significant compositional differences between children with MS and those who were normal weight or obese. At the class and genus levels, we found that the relative abundance of c_Gammaproteobacteria increased with weight, whereas c_Bacteroidia and g_Bacteroides decreased. Notably, g_Faecalibacterium was significantly less abundant in the MS group compared to the other cohorts. LEfSe and functional analyses identified distinct gut microbiota and functional differences between children with MS and those with normal weight or obesity. Furthermore, gavage experiments in mice showed that gut microbiota from obese and MS subjects significantly increased serum triglycerides and cholesterol levels, leading to hepatocellular damage. In contrast, fecal gavage from normal-weight individuals into obese model mice significantly reduced serum triglycerides and the number of degenerative liver cells, as well as the extent of fat accumulation. These findings provide critical insights into the understanding and management of obesity and metabolic syndrome in pediatric populations.